Respons terhadap Suplementasi Sabun Mineral dan Mineral Organik serta Kacang Kedelai Sangrai pada Indikator Fermentabilitas Ransum dalam Rumen Domba - . Adawiah; T Sutardi; T Toharmat; W Manalu; N Ramli; U H Tanuwiria (Media Peternakan, 2007)
The objective of this study was to evaluate the effect of supplementation with mineral soap, organic mineral and roasted soyabean on ration fermentability in the rumen of sheep. Thirty two Garut Sheep (initial weight 22.38 ± 3.56 kg) were assigned into a randomized complete block design with 8 treatments. Body weight was used as blocks (4 blocks). The treatments were FO: basal diet + fish oil, CO: basal diet + corn oil, CaFO: basal diet + calcium soap of fish oil, CaCO: basal diet + calcium soap of corn oil, ZnFO: basal diet + zinc soap of fish oil, ZnCO: basal diet + zinc soap of corn oil, RSB: basal diet + roasted soya bean, MM: basal diet + mineral mix (Zn, Cu, Cr, and Se-organic). The experimental diets were offered for 8 weeks. The results showed that ammonia concentrations of sheep fed CO, CaFO, CaCO, and MM were higher than those of sheep fed FO, ZnFO, ZnCO, RSB diets (9.28 v 6.75 mM). Vollatile fatty acid production was not affected by treatments (110.6 ± 7.69 mM). The levels of amonia and VFA in this experiment were suitable for microbial growth. Rumen bacterial population of sheep fed FO was the lowest (P < 0.05). Rumen protozoa population of sheep fed CO, CaFO, ZnFO, ZnCO, and MM were lower (P < 0.05) than those of sheep fed FO, CaCO, and RSB. It is concluded that supplemention of Ca-soap, organic minerals, and roasted soyabeans to sheep ration increased ration fermentability in the rumen. Ammonia and VFA concentrations were suitable for rumen microbial growth. Fat protection (Ca-soap) did not inhibit bacterial growth in the rumen. Key words: mineral soap, fish oil, corn oil, roasted soyabeans, fermentability